172 Increasing inclusion of fermentable fiber decreases nutrient digestibility in grower pigs - Heyer, Charlotte (J Anim Sci, 2020)
Fermentable fiber may increase endogenous losses of P and AA, thereby reducing apparent nutrient digestibility. Acacia gum fiber with medium-to-high fermentability and low viscosity was used to investigate its effect on apparent ileal digestibility (AID) and apparent total tract digestibility (ATTD) of nutrients, and standardized total tract digestibility (STTD) of P in grower pigs. A P-free basal diet (49% corn starch; 18% bovine plasma protein) was formulated to measure basal endogenous P losses (EPL). Three diets were formulated to include 2.5, 5.0, or 7.5% acacia gum fiber at the expense of corn starch in the P-free basal diet. Diets contained 16.1–17.4% CP and 0.31–0.33% total P (DM-basis). The 4 diets were fed to 8 ileal-cannulated barrows (initial BW, 54.6 kg) for four 9-d periods in a double 4 × 4 Latin square. Apparent hindgut fermentation (AHF) was ATTD minus AID. Increasing inclusion of acacia gum quadratically decreased (P < 0.01) AID of DM (∆ 11.1%), linearly decreased (P < 0.05) ATTD of DM (∆ 1.7%) CP (∆ 1.2%), and quadratically increased (P < 0.05) AHF of DM (∆ 9.4%). Basal EPL were 391 and 377 mg/kg DM intake (DMI) for ileum and total tract, respectively. Increasing inclusion of fiber linearly increased (P < 0.05) ileal EPL (∆ 184 mg/kg DMI), and tended to linearly increase (P < 0.10) EPL for total tract (∆ 243 mg/kg DMI). Dietary inclusion of acacia gum tended to linearly decrease (P < 0.10) AID of P, but did not affect (P > 0.10) ATTD, or STTD of P. In conclusion, increasing inclusion of fermentable, low viscous acacia gum fiber decreased diet digestibility of DM and ATTD of CP, but did not affect total tract P digestibility, indicating that increasing fermentable fiber did not increase specific endogenous losses of P in the total tract.